Functional implications of mitofusin 2-mediated mitochondrial-SR tethering. (January 2015) - Dorn, Gerald W.; Song, Moshi; Walsh, Kenneth
Abstract: Cardiomyocyte mitochondria have an intimate physical and functional relationship with sarcoplasmic reticulum (SR). Under normal conditions mitochondrial ATP is essential to power SR calcium cycling that drives phasic contraction/relaxation, and changes in SR calcium release are sensed by mitochondria and used to modulate oxidative phosphorylation according to metabolic need. When perturbed, mitochondrial-SR calcium crosstalk can evoke programmed cell death. Physical proximity and functional interplay between mitochondria and SR are maintained in part through tethering of these two organelles by the membrane protein mitofusin 2 (Mfn2). Here we review and discuss findings from our two laboratories that derive from genetic manipulation of Mfn2 and closely related Mfn1 in mouse hearts and other experimental systems. By comparing the findings of our two independent research efforts we arrive at several conclusions that appear to be strongly supported, and describe a few areas of incomplete understanding that will require further study. In so doing we hope to clarify some misconceptions regarding the many varied roles of Mfn2 as both physical trans-organelle tether and mitochondrial fusion protein. This article is part of a Special Issue entitled "Mitochondria: From Basic Mitochondrial Biology to Cardiovascular Disease." Highlights: Mitochondrial fusion proteins, mitofusins, are abundant in mammalian hearts. Cardiomyocyte mitochondria do not exhibit a fused morphology. Mitofusin (Mfn) 2 has secondary functions, including mitochondrial-SR tethering. Mfn2-mediated mitochondrial-SR tethering facilitates calcium cross-talk. Thus, Mfn2 modulates mitochondrial metabolism and MPTP opening.